Calcium signaling and expression of voltage-gated calcium channels in the mouse ovary throughout the estrous cycle†. Issue 4 (28th November 2018) - Bahena-Alvarez, Daniel; Rincón-Heredia, Ruth; Millán-Aldaco, Diana; Fiordelisio, Tatiana; Hernández-Cruz, Arturo
Abstract: The estrous cycle is an iterative change in the anatomy, endocrinology, physiology, and behavior to provide maximum fecundity. Ovarian steroid production involves gonadotropin-induced [Ca 2+ ]i raises due in part to voltage-gated Ca 2+ channels (VGCCs) whose identity and tissue distribution in situ is largely unknown. Using fluorescence Ca 2+ imaging and confocal microscopy, we recorded both spontaneous and depolarization-induced Ca 2+ signals in living mouse ovarian slices. They were most prominent in theca cells (TCs) and oocytes. The presence of Ca 2+ channel subunits CaV 1.2, CaV 1.3, CaV 2.1, CaV 2.2, and CaV 3 was examined with immunofluorescence of ovarian sections. CaV 1.2 and CaV 1.3 (L-type Ca 2+ channels) are present in the stroma, granulosa cells (GCs), and corpora lutea (CL). Intriguingly subunits that are characteristic of nerve cells are also expressed: P/Q-type (CaV 2.1; α1A) in the stroma and CL cells and N-type (CaV 2.2; α1B) in perifollicular smooth muscle cells. The expression of α1 subunits fluctuates along the estrous cycle: in metestrus-diestrus (the quiescent stage of the cycle), CL and GCs are similarly stained, while in proestrus (stage of maximal ovarian stimulation) CL staining increases relatively to GCs. Also in proestrus, CaV 3 Ca 2+ channel subunits are expressed more in CL compared to GC suggesting a more significant role of Ca 2+ channels. In estrus, CaV 3 subunits from mesenchymal and interfollicular stromal cells become intensely stained. Our study represents an important step in understanding the role of VGCCs in ovarian physiology and possibly in ovarian cancer and other reproductive pathologies. Abstract : Calcium signaling and the expression of voltage-gated Ca 2+ channels in the ovary is heterogeneous and varies considerably along the estrous cycle.